An Intuitive Approach for Predicting Potential Human Health Risk with the Tox21 10k Library - Sipes, Nisha S. (Environ Sci Technol, 2017)
In vitro-in vivo extrapolation (IVIVE) analyses translating high-throughput screening (HTS) data to human relevance have been limited. This study represents the first report applying IVIVE approaches and exposure comparisons using the entirety of the Tox21 federal collaboration chemical screening data, incorporating assay response efficacy and quality of concentration-response fits, and providing quantitative anchoring to first address the likelihood of human in vivo interactions with Tox21 compounds. This likelihood was assessed using a maximum blood concentration to in vitro response ratio approach (C(max)/AC(50)), analogous to decision-making methods for clinical drug-drug interactions. Fraction unbound in plasma (f(up)) and intrinsic hepatic clearance (CL(int)) parameters were estimated in silico and incorporated in a 3-compartment toxicokinetic (TK) model to first predict C(max) for in vivo corroboration using therapeutic scenarios. Toward lower exposure scenarios, 36 compounds of 3,925 with curated activity in the HTS data using high quality dose-response model fits and ≥40% efficacy gave ‘possible’ human in vivo interaction likelihoods lower than median human exposures predicted in EPA’s ExpoCast program. A publicly available web application has been designed to provide all Tox21/ToxCast dose likelihood predictions. Overall, this approach provides an intuitive framework to relate in vitro toxicology data rapidly and quantitatively to exposures using either in vitro or in silico derived TK parameters, and can be thought of as an important step towards estimating plausible biological interactions in a high throughput risk assessment framework.